Distribution and risk factor analysis for Clostridium difficile‐associated diarrhea among hospitalized children over one year of age - Chunna Zhao; Shu Guo; Xiaoyun Jia; Xiwei Xu (Wiley, 2020)
ABSTRACT Importance Clostridium difficile‐associated diarrhea (CDAD) is a severe type of antibiotic‐associated diarrhea (AAD). However, the risk factors for CDAD in children with AAD have not yet been clarified. Objective To investigate the distribution and risk factors for CDAD among hospitalized children in Beijing Children's Hospital. Methods Stool samples from 197 children with AAD were tested for the C. difficile pathogenic genes (tcdA, tcdB, tcdC, tcdD, tcdE, cdtA, and cdtB) using polymerase chain reaction between January 2011 and January 2014. Children who tested positive for tcdA or tcdB were included in the CDAD group, and those remaining comprised the non‐CDAD group. Results The rate of CDAD among the 197 children with AAD was 42.6% (84/197). The age distribution was 1-15.6 years, among which the majority of children (54.8%, 46/84) were aged 1-4 years. Differences in the CDAD‐positive rates among AAD children belonging to different age groups were not statistically significant. Univariate analysis revealed that the duration of antibiotic therapy, the length of hospitalization prior to diarrhea, and gastrointestinal tract operations were significant risk factors (P < 0.05). Children with CDAD underwent more antibiotic therapy and had longer periods of hospitalization prior to diarrhea onset than children in the non‐CDAD group. Using multivariate regression analysis, hospitalization for ≥ 10 days prior to diarrhea was found to be an independent risk factor for CDAD. Interpretation This study revealed that the length of hospitalization (≥ 10 days) prior to diarrhea was an independent risk factor for CDAD in children with AAD.